EFFECT OF CUCUMBER (CUCUMIS SATIVUS) JUICE ON LOWERING BLOOD PRESSURE IN ELDERLY - Pertami, Sumirah Budi; Rahayu, Dian Yuniar Syanti; Budiono, Budiono (YCAB Publisher & IAKMI SULTRA, 2017)
Background: Hypertension is one of the diseases that cause high morbidity. The use of modern hypertension medical treatment may cause a side effect, so cucumber as one of traditional medicines may become a choice.Objective: This study aims to see the effect of cucumber (Cucumis sativus) juice on lowering blood pressure in elderly at working area of Puskesmas (public health center) of Abeli, Kendari, 2015.Methods: This was a pre-experiment study with one group pretest-posttest design. Twenty elderly > 60 years old were selected by simple random sampling.Results: The result showed that there was a significant effect of cucumber juice on lowering blood pressure in elderly people at working area of Puskesmas of Abele, with t test for systolic blood pressure showed that t count > t table (7.095>2.093) or P-value is 0.000 < 0.05; and t test for diastolic blood pressure showed that t count > t table (6.190>2,093) or P-value is 0.000 < 0.05.Conclusion: The significant effect of cucumber (Cucumis sativus) juice on lowering blood pressure in elderly suggested that health professional might need to have the cucumber to deal with hypertension. However, further study is needed to examine the effect.